2001
DOI: 10.1128/jvi.75.3.1211-1219.2001
|View full text |Cite
|
Sign up to set email alerts
|

Proteinase-Polymerase Precursor as the Active Form of Feline Calicivirus RNA-Dependent RNA Polymerase

Abstract: The objective of this study was to identify the active form of the feline calicivirus (FCV) RNA-dependent RNA polymerase (RdRP). Multiple active forms of the FCV RdRP were identified. The most active enzyme was the full-length proteinase-polymerase (Pro-Pol) precursor protein, corresponding to amino acids 1072 to 1763 of the FCV polyprotein encoded by open reading frame 1 of the genome. Deletion of 163 amino acids from the amino terminus of Pro-Pol (the Val-1235 amino terminus) caused a threefold reduction in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
69
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(74 citation statements)
references
References 25 publications
4
69
1
Order By: Relevance
“…The addition of rifampicin to the reaction did not interfere with RNA synthesis, indicating that any host factors carried over during the purification step were not responsible for the RNA-synthesis activity. Based on these results, we concluded that recombinant MNV-1 3D pol retains its RdRp activity, as reported for other caliciviruses (Belliot et al, 2005;Fukushi et al, 2004;Fullerton et al, 2007;Morales et al, 2004;Ló pez Vázquez et al, 1998Rohayem et al, 2006a, b;Wei et al, 2001). .…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The addition of rifampicin to the reaction did not interfere with RNA synthesis, indicating that any host factors carried over during the purification step were not responsible for the RNA-synthesis activity. Based on these results, we concluded that recombinant MNV-1 3D pol retains its RdRp activity, as reported for other caliciviruses (Belliot et al, 2005;Fukushi et al, 2004;Fullerton et al, 2007;Morales et al, 2004;Ló pez Vázquez et al, 1998Rohayem et al, 2006a, b;Wei et al, 2001). .…”
Section: Discussionmentioning
confidence: 72%
“…Recombinant forms of the uncleaved proteinase-polymerase (Pro-Pol) precursors of feline calicivirus (FCV) and HuNV (Belliot et al, 2005;Wei et al, 2001), along with mature RdRps of HuNV, rabbit hemorrhagic disease virus (RHDV) and sapovirus, exhibit RNA-synthesis activity in vitro (Fukushi et al, 2004;Fullerton et al, 2007;Ló pez Vázquez et al, 1998Morales et al, 2004;Rohayem et al, 2006a, b).…”
Section: Introductionmentioning
confidence: 99%
“…Although some variation has been observed among caliciviruses in their processing strategies to release the final mature nonstructural proteins (14,19,30,32,34), the accumulation of the stable MD145-12 precursor proteins p20VPg and ProPol, similar to those identified in cell culture studies of FCV and RHDV, suggests that these proteins are important in the calicivirus replication strategy. Of interest, these precursor proteins are likely analogous to the picornavirus 3AB and 3CD proteins, respectively (14,30,32,33). One striking difference between the noroviruses in comparison with FCV and RHDV is the absence of an intermediate precursor containing part of the N-terminal protein (possibly the picornavirus 2B equivalent) complexed with the NTPase (p71 for FCV and p60 for RHDV) (19,30).…”
Section: Discussionmentioning
confidence: 99%
“…The ORF1 (nucleotides 20-5305) encodes a large polyprotein, which undergoes cotranslational cleavage yielding 6 nonstructural proteins ranging in size from 5.6 to 75.6 kD. 4,33,36,43 The ORF2 (nucleotide 5314 to 7317-7326) encodes the precursor of the major structural capsid protein, 5,22 which later undergoes cleavage by a viral-encoded proteinase to a 65-66-kD mature protein. 35 The capsid protein is divided into 6 areas on the basis of genetic variability, designated A, B, C, D, E, and F representing amino acids residues 1-120, 121-396, 397-401, 402-425, 426-520, and 521-668, respectively.…”
Section: Introductionmentioning
confidence: 99%